Affective factors that influence english oral production in the 8th level students of basic general education at Juan Pablo II high school in Ibarra - Morales Cruz, Sandra Yomira (2022)
Apply methodological strategies to manage the affective factors in English oral production, in order to enhance self-esteem and minimize anxiety in 8th level students at Juan Pablo II High school.